2013
DOI: 10.1387/ijdb.130028pk
|View full text |Cite
|
Sign up to set email alerts
|

Nodal/Cripto signaling in fetal male germ cell development: implications for testicular germ cell tumors

Abstract: Testicular cancer is the most frequent cancer in young men aged 15-40 years and accounts for 1% of all cancer diagnosed in males. Testicular germ cell tumors (TGCT) encompass a broad group of cancers, each displaying different levels of pluripotency and differentiation as well as malignancy potential. The TGCT cell of origin is thought to be a fetal germ cell that failed to correctly differentiate during development: this is known as the 'fetal origins hypothesis' . This theory predicts that developmental path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 107 publications
2
19
0
1
Order By: Relevance
“…The NODAL/CRIPTO signaling pathway is believed to regulate the delicate balance between the proliferation of germ cells and fate commitment, meaning that disturbance of this signaling cascade may lead both to infertility (due to insufficient spermatogonial stem cells) or to prolonged pluripotency, resulting in the development of TGCTs [14]. This is in line with the finding of ectopic NODAL/CRIPTO signaling activation in NS [15]. CRIPTO was also found to be at least partially regulated by promoter methylation [16,17].…”
Section: Introductionsupporting
confidence: 78%
“…The NODAL/CRIPTO signaling pathway is believed to regulate the delicate balance between the proliferation of germ cells and fate commitment, meaning that disturbance of this signaling cascade may lead both to infertility (due to insufficient spermatogonial stem cells) or to prolonged pluripotency, resulting in the development of TGCTs [14]. This is in line with the finding of ectopic NODAL/CRIPTO signaling activation in NS [15]. CRIPTO was also found to be at least partially regulated by promoter methylation [16,17].…”
Section: Introductionsupporting
confidence: 78%
“…We recently discovered that the TGFβ signaling molecule Nodal and its obligate receptor Cripto are expressed at a critical point during fetal XY germ cell development in mice and that Nodal/Cripto signaling is active, apparently acting to maintain pluripotency and oppose differentiation (Spiller et al., 2012). We also found that Nodal/Cripto signaling is ectopically activated in NS and we therefore hypothesize that ectopic activation of Nodal signaling, or failure to silence it, contributes to GCC formation (Spiller et al., 2013).…”
Section: Introductionmentioning
confidence: 87%
“…Type II TGCC are divided into two categories: seminomas which resemble a less aggressive carcinoma in-situ, and non-seminomas which display a high degree of pluripotency factors [106]. Non-seminomas form highly heterogeneous tumors with both differentiated and undifferentiated cells forming teratomas and choriocarcinomas and display more embryonal-like features.…”
Section: Nodal and Cancermentioning
confidence: 99%